Programação para administração de redes de computadores: guia didático para professores - Oliveira, Silmar Antonio Buchner de (2018)
In this guide we present a teaching-learning proposal of programming for Computer Network administration, considering the context of undergraduate courses in Computing area. This is an educational product from a research developed in the Professional Master's Degree in Technology Teaching (MPET) of the Federal Institute of Education, Science and Technology of Amazonas (IFAM), Campus Manaus Centro and is intended for teachers of higher education in computing that teach disciplines of Computer Networks. We did this proposal as an alternative that provides a practical learning for disciplines of Computer Networks taught in higher courses, where the student learns to solve problems of Computer Networks with the use of Programming, with "hands on" approach. In addition to providing an increase in learning in both Computer Networks and Programming, this teaching proposal offers the student the skills improvement that is required in the professional world. To achieve these goals and place the student at the center of their learning, we adopted the flipped classroom format where students exercises the theory outside the classroom environment, while in class use the time and interaction with the teacher to solve practical problems involving the monitoring of network equipments and user actions, log analysis, synchronization of data and automatic issuance of alert messages. In order for other teachers to reproduce this experience, we created this guide where we provide all the required material, including videos, learning guides, guidelines for virtual laboratory creation, links, tutorials and suggestions on general procedures. In addition, we offer a set of student orientations so that teachers can guide them on how to develop their potential and achieve better learning outcomes.